Cu-doped polymeric carbon nitrides: structural and electronic properties and sensitivity to flue gas - Gouveia, José D. (2024)
The global warming of the Earth and its adverse effects on the climate system is one of the greatest challenges that humanity faces today and one way to mitigate its development is to control the emissions of greenhouse gases, which can be done with the utilization of suitable adsorbent materials. Recently, polymeric carbon nitrides (PCN) doped with single or geminal copper atoms were experimentally obtained and found to be interesting for catalytic applications. In this work, we study the electronic properties of the bare and copper containing PCN materials and analyse their potential for sensing or adsorption/separation applications of main constituents of flue gas. Our results indicate that Cu4PCN is a semiconductor with a band gap energy of 1.43 eV, which can be reduced by adsorbing flue gas molecules. Many of these chemisorb, with adsorption energies up to -0.64 eV, and all of them become negatively charged, by up to -0.35 e. The Cu4PCN surface is especially sensitive to NO, O2, SO2 and SO3, which display some of the strongest adsorptions and charge transfers, along with the most significant changes in the band gap of Cu4PCN, changing its conductivity and allowing detection.